Blue ocean shift : beyond competing : proven steps to inspire confidence and seize new growth - Kim, W. Chan; Mauborgne, Renée (Hachette Books, 2017)
Following up on 2015's Blue Ocean Strategy, Drs. W. Chan Kim and Reneé Mauborgne show you how to move beyond competing, inspire your people's confidence, and seize new growth. They guide you step-by-step through taking your organization from a red ocean crowded with competition to a blue ocean of uncontested market space. By combining the insights of human psychology with practical market-creating tools, Kim and Mauborgne deliver a guide to shift yourself, your team, or your organization to new heights of confidence, market creation, and growth. They show why nondisruptive creation is as important as disruption in seizing new growth. Whether you are a cash-strapped startup or a large, established company, nonprofit or national government, you will learn how to move from red to blue oceans in a way that builds your people's confidence so that they own and drive the process